Synthesis, Characterization and Application of Hybrid Composites - Blanco, Ignazio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Polymer composites represent the platform materials of the XXI century and are an important slice of the market in the production of modern plastics. Their design is based on adding a second component to the polymer matrix to enhance its properties. Among the various possible composites, organic-inorganic hybrid materials offer advantageous performance relative to either of the non-hybrid counterparts. The dramatic improvement of physical properties, compared with pure materials, in which inorganic particles or nanoparticles are inserted into an organic polymeric matrix, could bridge the gap between ceramics and polymers. We are interested in articles that explore polymer-based hybrid systems. The Special Issue topics include the synthesis and characterization of polymeric hybrid materials-hybrid composites in electronics and energy applications; hybrid composites in space applications; the biomedical application of hybrid polymeric materials.